Occurrence, distribution and threats to mobulid rays in Brazil: A review and updated database - Bucair, Nayara (2024)
Mobulid rays are medium- to large-sized pelagic-dwelling planktivorous elasmobranchs that are circumglobally distributed. Brazil has a high diversity of Mobula species, with five of the nine globally valid species and one additional putative new species. Brazil represents a substantial knowledge gap concerning the ecology, distribution and threats to mobulid rays. In global distribution analyses, several species have been underrepresented along the Brazilian coast. The dataset is composed of information from peer-reviewed and grey literature, as well as data from scientific expeditions, citizen science collaboration, social media and local news. We found 6,450 records of manta and devil rays along the Brazilian coast, including Mobula tarapacana, Mobula mobular, Mobula thurstoni, Mobula hypostoma, Mobula birostris and the putative new species (Mobula cf. birostris). Our results revealed alarmingly high captures, such as 4.5 tons of M. hypostoma in a single fishery cruise and 809 individuals of Mobula spp. from a single fleet during one year in the Southeastern region. These findings evidence the fisheries' threats to mobulid species in Brazil and highlight previously unnoted species records, such as the occurrence of M. hypostoma on the entire Brazilian continental shelf, including estuaries and M. tarapacana in coastal regions. Integrative information on the occurrence, distribution, and threats to mobulid rays on local and global scales is crucial to supporting strategies for their effective management and conservation.